2021
DOI: 10.1016/j.jaerosci.2020.105693
|View full text |Cite
|
Sign up to set email alerts
|

Breath-, air- and surface-borne SARS-CoV-2 in hospitals

Abstract: The COVID-19 pandemic has brought an unprecedented crisis to the global health sector. When discharging COVID-19 patients in accordance with throat or nasal swab protocols using RT-PCR, the potential risk of reintroducing the infection source to humans and the environment must be resolved. Here, 14 patients including 10 COVID-19 subjects were recruited; exhaled breath condensate (EBC), air samples and surface swabs were collected and analyzed for SARS-CoV-2 using reverse transcription-polymerase chain reaction… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
87
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(92 citation statements)
references
References 15 publications
5
87
0
Order By: Relevance
“…Meanwhile, it is also suggested to integrate robot with the gas release system to sterilise the area and prevent disease spreading [ 43 ]. In an application in China, a robot was also utilised to collect air samples in the hospital [ 44 ]. Robotics is needed in an advanced HealthTech ecosystem, together with photonics, biomaterials, smart systems, digital health and textile [ 45 ].…”
Section: Robots In Covid-19mentioning
confidence: 99%
“…Meanwhile, it is also suggested to integrate robot with the gas release system to sterilise the area and prevent disease spreading [ 43 ]. In an application in China, a robot was also utilised to collect air samples in the hospital [ 44 ]. Robotics is needed in an advanced HealthTech ecosystem, together with photonics, biomaterials, smart systems, digital health and textile [ 45 ].…”
Section: Robots In Covid-19mentioning
confidence: 99%
“…This led researchers to explore alternative specimen types such as breath, odor, and saliva. There has been an increased interest in screening for COVID-19 via collection of exhaled breath for direct virus detection [120]; however, this method requires further clinical evaluation to determine the reliability and accuracy. Saliva is a promising sample for COVID-19 testing because it is easy and painless to collect and seemingly has a high viral load [121].…”
Section: Lamp For Covid-19 Detectionmentioning
confidence: 99%
“…During 2020, the human race suffered from the COVID-19 pandemic (1-6) but fortunately learned the importance of controlling transmission through air (7)(8)(9)(10)(11). As a main source of aerosol spread of respiratory viruses, exhaled breath of patients has been confirmed as a potential risk using various methods of sampling and subsequent testing (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). Several groups have reported SARS-CoV-2 positivity in samples of exhaled breath condensate (EBC) (21)(22)(23)(24)(25), and based on Ct values, Ma et al further showed that EBC-positive COVID-19 patients exhaled millions of SARS-CoV-2 RNA copies per hour (23).…”
Section: Introductionmentioning
confidence: 99%
“…As a main source of aerosol spread of respiratory viruses, exhaled breath of patients has been confirmed as a potential risk using various methods of sampling and subsequent testing (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). Several groups have reported SARS-CoV-2 positivity in samples of exhaled breath condensate (EBC) (21)(22)(23)(24)(25), and based on Ct values, Ma et al further showed that EBC-positive COVID-19 patients exhaled millions of SARS-CoV-2 RNA copies per hour (23). Standard diagnosis of viruses based on swabs or serum has been rapidly developed (17,(26)(27)(28)(29), while auxiliary methods, such as trace biomarkers of COVID-19 in exhalations, have also been explored (18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%